Manejo integrado de Perileucoptera coffeella (Guérin-Méneville, 1842) en el cultivo de café - Piza Villamar, Hermes Alejandro (2023)
The cultivation of coffee (Coffea spp.) is one of the crops of economic importance worldwide. Its importance also lies, in addition, for providing one of the drinks consumed worldwide. In Ecuador, the main coffee producing provinces are El Oro, Manabí, Loja, Guayas, Los Ríos, Santa Elena, Orellana and Zamora Chinchipe. Unfortunately, this crop is susceptible to attack by P. coffeella Guerin-Meneville, which annually registers an increase in the incidence of attack and a decrease in national production. This work aims to detail the damage caused and refer to the main control methods of the coffee leaf miner P. coffeella. The larval stage of P. coffeella consumes an average of 1 to 2 cm2 of leaf mesophyll area. Consumption that worsens when there are several larvae in a single mine causing necrosis. Leaf necrosis can reach 90% and cause a loss of 50% of production. The control methods reported for the coffee leaf miner after evaluating and verifying the threshold of 30% of active mines are the cultural control method, the natural biological control method, the genetic control method and the control and chemical Chemical control is the option most used by the farmer to control P. coffeella in coffee cultivation.